Analysis of pilot as a dynamic link in the system "aircraft-pilot-environment-special situation" - Попов, П.В.; Тачиніна, О.М. (Proceedings of National Aviation University (archive), 2006)
The analysis of dynamic behavior of pilot as section of system “аircraft – flight pilot – environment – abnormal situation” has been carried out. Moreover the expediency of elaboration of the mathematical model of pilot that enables to forecast pilot response under abnormal situation during flight and to develop recommendations for personnel of flight simulator centers concerning acquisition by pilots of skill required to make decision in abnormal situation during flight has been proved.